The unpolarized TMD valence quark distributions of light mesons in the statistical covariant parton model approach - P. Abolhadi; M. M. Yazdanpanah; H. Nematollahi (European Physical Journal C: Particles and Fields, 2023)
Abstract We investigate the unpolarized transverse momentum dependent (TMD) structure of light mesons at low $$Q^2$$ Q 2 scales in nonperturbative region of quantum chromodynamics (QCD). To this end, we calculate the unpolarized TMD valence quark distribution functions of pion and kaon based on the covariant parton model in which the flavour dependent covariant momentum distribution of quarks is needed. We apply the statistical model for this momentum distribution, for the first time, and also consider the quarks to be massive. The results of TMD valence distributions of light mesons show convenient general properties. We also obtain the integrated valence quark distributions of pion and kaon and compare our results with those of other models.